The Influence of Computation Implementation in Chemistry Basic Courses on Chemistry-Biology Pre-Service Teachers of UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan - Nasution, Annisa; Hasibuan, Fadli Mahmul; Simanjuntak, Rizki Agus Salim (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This study aims to determine the effect of the implementation of computation through the experimental test method on the skills of students majoring in Tadris Biology UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan 3rd semester. This type of research is experimental research with a pretest-posttest control group design. Sampling was carried out using cluster random sampling technique. The population in this study were students of Tadris Biology at Uin Shahada Padangsidimpuan, with a sample of Tadris Biology students at UIN Syahada (experimental class) and Tadris Biology students at Uin Shahada Padangsidimpuan Semester 3 (control class). The instrument used was a process skill test in the form of reasoned multiple choice which was first tested for validity, reliability. The results of the pretest homogeneity test showed the initial ability of the experimental class and homogeneous control, so that the effect of the treatment was the result of the posttest. So, it can be concluded that there is an effect of computer-based learning through experimental methods on the influence of the implementation of computing in basic courses on students of Tadris Biology at Uin Shahada Padangsidimpuan.